Factors Contributing to Outcomes of the Pmtct Intervention in the Western Region of Ghana - Amo-Addae, P. K. (University of Ghana, 2015)
Background: In 2009, when the UNAIDS called for the elimination of mother-to-child transmission of HIV (MTCT) by 2015, Ghana was found to be one of 20 countries accounting for 80% of the global burden of prevention of MTCT (PMTCT). MTCT is the main source of pediatric HIV, accounting for over 90% of cases worldwide. This study contributes to the assessment of Ghana‟s performance towards achieving the elimination of MTCT. The study described the coverage and outcomes of the PMTCT intervention from 2010 to 2013, assessed the knowledge of midwives regarding the intervention and sought to identify maternal and pregnancy-related factors contributing to PMTCT outcome by 6weeks after delivery in the Western Region of Ghana. Methods: Quantitative and qualitative methods were applied in the study. Records reviews and indepth interviews were conducted to describe the PMTCT coverage and outcomes and to assess the knowledge and practices of midwives implementing PMTCT. A nested case control design was used to determine factors contributing to PMTCT outcome. The Epiinfo statistical package was used for the analysis. Results: Facilities providing PMTCT services are available in all districts of the Region. However, 42 private facilities and CHPS compounds* offering ANC services within these districts do not conduct HIV testing for clients. From 2010 to 2013, a total of 36.3% of ANC clients (147,990 out of 408,201) were not tested for HIV. However, the prevalence of HIV among the ANC clients tested in the Region shows a downward trend from 2.3% in 2010 to 1.9% in 2013. There is low patronage of the early infant diagnosis (EID) service at the Regional Public Health Laboratory. EID records were available for only 13.4% of exposed babies from November 2011 to November 2013. Midwives providing the PMTCT service were unaware of the PMTCT national target and had weak follow-up systems to trace defaulting clients. Spousal influence and fear of the unknown was the main reason for opting out of HIV testing at ANC. None of the maternal and pregnancy-related variables studied (including age, concurrent illness, IPT compliance and birth order) was found to contribute significantly to PMTCT outcomes in the Western Region but twin delivery and female sex had higher risk of MTCT. The MTCT rate was 5.5% among a group of mothers and their babies whose ART history could not be ascertained, but surprisingly higher at 12.1% among PMTCT clients who had benefitted from ART. Conclusion: There is adequate distribution of PMTCT services in the Western Region of Ghana. An MTCT rate of 5.5% to 12% was observed. Some gaps identified in achieving elimination of MTCT were the non-availability of HIV testing at some ANC sites, missed opportunities for HIV testing at ANC clinics and low knowledge and patronage of EID by midwives and their clients resulting in the loss of many babies along the continuum of care. Twin gestation and having a female baby may be associated with higher MTCT risk but this requires further research. Key words: PMTCT, MTCT, risk, elimination, outcomes, ANC, EID *Community-based Health Planning and Services (CHPS) compounds are primary level healthcare facilities operating at the community.
Thesis (MPhil) - University of Ghana, 2015